Implementation Deep Learning Method On Decision Support System For Smart Indonesia Card Scholarship At University Of KH. Bahaudin Mudhary Madura - Mohammad Iqbal Bachtiar; Rachmad Hidayat (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Scholarships are financial aid or funds awarded to individuals or groups to support education, research, or other academic development. There are many types of scholarships such as academic achievement scholarships, non-academic achievement scholarships, financial scholarships, and others. College scholarships are financial aid or funds provided to students to assist them in their pursuit of higher education. Scholarships in tertiary institutions can be full such as smart card scholarships or partial such as free tuition scholarships, and the aim is to encourage wider access to education and help students who are talented but face financial constraints in pursuing their education. At the University of KH. Bahaudin Mudhary Madura for scholarship applicants there are very many, there are hundreds or even nearly thousands of students who register, especially on the smart Indonesian card scholarship and this also requires very fast time and a good level of accuracy in decision making. Therefore, it requires a decision support system. In this study, the deep learning method was applied to a decision support system with a loss of 1.43%, an accuracy rate of 98.57% and a system runtime of 77ms/step.